Decreased risk of radiation pneumonitis with concurrent use of renin-angiotensin system inhibitors in thoracic radiation therapy of lung cancer - Zheng, Yawen; Cong, Changsheng; Wang, Zewen; Liu, Yanan; Zhang, Mingyan; Zhou, Hao; Su, Chen; Sun, Meili (Frontiers in Medicine, 2023)
Background: Radiation pneumonitis (RP) is the primary dose-limiting toxicity associated with radiotherapy. This study aimed to observe the effects of renin-angiotensin system inhibitors in Chinese patients with lung cancer who received thoracic radiation.Patients with lung cancer who received thoracic radiation at a total dose of ≥ 45 Gray between October 2017 and December 2022 were enrolled in this study. We retrospectively evaluated the factors influencing grade 2 or higher RP.Results: A total of 320 patients were enrolled in this study; 62 patients were identified as angiotensin receptor blockers or angiotensin-converting enzyme inhibitor users. Additionally, 99 patients (30.9%) had grade 2 or higher RP, and the incidence in the renin-angiotensin system inhibitor group was 17.7% (11 out of 62 patients). Patients in the renin-angiotensin system inhibitors (RASi) group were older and had a higher percentage of males, lower percentage of ECOG score 0, higher percentage of hypertension, and higher percentage of adenocarcinoma than those in the non-RASi group. ECOG score (hazard ratio [HR] = 1.69, P = 0.009), history of smoking (HR = 1.76, P =0.049), mean dose (HR=3.63, P = 0.01), and RASi (HR=0.3, P=0.003) were independent predictive factors for RP. All subgroups benefited from RASi. This is a provisional file, not the final typeset article Conclusion: This study showed that oral RASi administration has the potential to mitigate the incidence of grade 2 or higher RP in patients with lung cancer undergoing thoracic radiotherapy. To validate and further substantiate these findings, additional prospective research is warranted.